A review of uncertainties in radiotherapy dose reconstruction and their impacts on dose–response relationships. (24th January 2017) - Vũ Bezin, Jérémi; Allodji, Rodrigue S; Mège, Jean-Pierre; Beldjoudi, Guillaume; Saunier, Fleur; Chavaudra, Jean; Deutsch, Eric; de Vathaire, Florent; Bernier, Valérie; Carrie, Christian; Lefkopoulos, Dimitri; Diallo, Ibrahima
Abstract: Proper understanding of the risk of radiation-induced late effects for patients receiving external photon beam radiotherapy requires the determination of reliable dose–response relationships. Although significant efforts have been devoted to improving dose estimates for the study of late effects, the most often questioned explanatory variable is still the dose. In this work, based on a literature review, we provide an in-depth description of the radiotherapy dose reconstruction process for the study of late effects. In particular, we focus on the identification of the main sources of dose uncertainty involved in this process and summarise their impacts on the dose–response relationship for radiotherapy late effects. We provide a number of recommendations for making progress in estimating the uncertainties in current studies of radiotherapy late effects and reducing these uncertainties in future studies.